Managing Contingent Liabilities in Public-Private Partnerships : Practice in Australia, Chile, and South Africa - Irwin, Timothy; Mokdad, Tanya (World Bank, Washington, DC, 2015)
Contingent liabilities create management problems for governments. They have a cost, but judging what the cost is and whether it is worth incurring is difficult. Except in the case of contingent liabilities created by simple guarantees of debt, governments usually can incur contingent liabilities without budgetary approval or recognition in the governments accounts. So governments may prefer contingent liabilities to other obligations. (The uncertainty surrounding contingent liabilities can work differently. It is well known that PPPs create contingent liabilities, and the International Monetary Fund (IMF), the World Bank, and others often warn of the risks. The initial reaction of a cautious Ministry of Finance may be to seek to avoid all contingent liabilities.) Management problems also arise once a government has incurred a contingent liability. Projects need to be monitored to reduce risks if possible. Spending on contingent liabilities must sometimes be forecast, despite the difficulty.